2020
DOI: 10.3390/children7120277
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Parents in Analgesia Selection and Racial/Ethnic Differences in Analgesia Given to Pediatric Patients Undergoing Urologic Surgery

Abstract: Background: Family-centered care aims to consider family preferences and values in care delivery. Our study examines parent decisions regarding anesthesia type (caudal regional block or local anesthesia) among a diverse sample of children undergoing urologic surgeries. Differences in anesthesia type were examined by known predictors of health disparities, including child race/ethnicity, parental English proficiency, and a proxy for household income. Methods: A retrospective review of 4739 patients (including 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Lo et al performed a single-center retrospective study of pediatric patients < 6 years of age who were offered caudal block for urologic surgery. They found that parents of Black and Latinx children were less likely to consent to caudal block than parents of White children [ 57 ]. The authors did not find a disparity in consent by parental primary language.…”
Section: Intraoperative Racial Disparitiesmentioning
confidence: 99%
“…Lo et al performed a single-center retrospective study of pediatric patients < 6 years of age who were offered caudal block for urologic surgery. They found that parents of Black and Latinx children were less likely to consent to caudal block than parents of White children [ 57 ]. The authors did not find a disparity in consent by parental primary language.…”
Section: Intraoperative Racial Disparitiesmentioning
confidence: 99%
“…Adult studies have addressed health care inequities based on ethnicity, race, and socioeconomic factors, but there are few inequity studies focused on children in the perioperative period. Lo et al found that Latino and Black children were less likely to receive a caudal regional block than other racial sub-groups for urologic surgery [ 18 ]. Dixit et al found that although low English proficiency patients received the same amount of opioid medication intraoperatively, these patients had double the odds of receiving opioids in the recovery unit and received higher oral morphine equivalents than English proficient patients [ 19 ].…”
Section: Health Care Inequitiesmentioning
confidence: 99%
“…An important topic of research involves defining differences in rates of RA use. In the pediatric setting, black patients were less likely to receive local anesthesia for inguinal hernia repair14 and demonstrated lower rates of family approval among pediatric urology patients 15. Minority obstetric patients (ie, African–American, Hispanic) were less likely to receive neuraxial anesthesia (NA) for cesarean delivery than non-minority women,16 17 and black and Asian postmastectomy patients had lower odds of RA receipt 18.…”
Section: Introductionmentioning
confidence: 99%